Plasma and Urinary Oxytocin Trajectories in Extremely Premature Infants During NICU Hospitalization. (October 2017) - Weber, Ashley; Harrison, Tondi M.; Sinnott, Loraine; Shoben, Abigail; Steward, Deborah
Extremely premature infants are at great risk for poor neurodevelopmental outcomes, in part because neurologic structures designed to mature in the womb must now do so in the extrauterine environment. Reliable biomarkers of neurodevelopment are especially critical in this population, as behavioral measures can be unreliable due to immaturity of the premature infant nervous system. Oxytocin (OT) has the potential to be a marker of neurobiological processes that offer infant neuroprotection. However, no studies have measured OT in the plasma and urine of premature infants. The purposes of this study were to describe plasma and urine OT levels of premature infants through 34 weeks corrected gestational age (CGA), determine whether plasma and urine OT are correlated, and explore associations between infant demographics and OT trajectories. Plasma and urine from 37 premature infants, born at gestational ages 25–28 6/7 weeks, were longitudinally collected at 14 days of life, then weekly until 34 weeks CGA. Plasma OT decreased with age, at a rate of 15% per week, and exhibited strong stability within infants. Urine OT was not correlated with plasma OT and did not show a significant trend over time; thus, urine may not be a reliable, noninvasive measurement in this population. Apgar score was the only infant demographic characteristic associated with plasma OT. Given the novelty of this work, replication is needed to confirm these findings, and future research should explore potential mechanisms (e.g., stress, normal maturation, and social experiences) that contribute to declining plasma OT levels in premature infants.